2016
DOI: 10.1007/s00572-016-0726-z
|View full text |Cite
|
Sign up to set email alerts
|

Igneous phosphate rock solubilization by biofilm-forming mycorrhizobacteria and hyphobacteria associated with Rhizoglomus irregulare DAOM 197198

Abstract: Biofilm formation on abiotic and biotic surfaces was studied with two hyphobacteria, strongly attached to the surface of the arbuscular mycorrhizal fungus (AMF) Rhizoglomus irregulare (Ri) DAOM 197198 and two mycorrhizobacteria, loosely attached to the roots of different mycorrhizal plants. When the sparingly soluble igneous phosphate rock (PR) from Quebec, or when the chemical hydroxyapatite were used as sole phosphorus (P) source, hyphobacteria Rhizobium miluonense Rm3 and Burkholderia anthina Ba8 produced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 53 publications
2
33
0
2
Order By: Relevance
“…Our findings are also in agreement with those documented by many scientists 49 – 54 who reported that PSB release organic acids, lowering the pH of the surrounding soil and thereby solubilizing the fixed calcium phosphate in alkaline soil. Organic acids use their hydroxyl and carboxyl groups to chelate the cations (Ca, Al, Fe) bound to phosphorus and release the P 55 . Alori et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also in agreement with those documented by many scientists 49 – 54 who reported that PSB release organic acids, lowering the pH of the surrounding soil and thereby solubilizing the fixed calcium phosphate in alkaline soil. Organic acids use their hydroxyl and carboxyl groups to chelate the cations (Ca, Al, Fe) bound to phosphorus and release the P 55 . Alori et al .…”
Section: Discussionmentioning
confidence: 99%
“…Operons encoding proteins from each of these processes were DE, all being in higher abundance in contaminated conditions. The formation and adhesion of bacterial biofilms to fungal hyphae has been well characterised as facilitating the exchange of nutrients [ 28 , 29 ] but has also been shown to allow the mobilisation of pollutant degrading bacteria through the environment for mutual benefit [ 175 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peril of confounding bacterial community assessment by culturing methodology alone is also widely acknowledged, but the progression of contemporary sequencing techniques and extensive research advancement driven by fields relating to the human microbiome has led to an understanding of the ubiquitous, exceedingly diverse, presence and involvement of bacteria in eukaryotic biology. The importance of bacteria to mycorrhizal fungi and/or plant health has been established even in conditions less challenging than anthropogenic soil contamination [ 25 28 ]. Bacteria whose presence and function is beneficial to mycorrhizal fungi and/or plants are often termed mycorrhizal helper bacteria MHB [ 29 , 30 ] or plant growth-promoting bacteria (PGPB), such as the recently identified Enterobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…Karagöz et al [41] revealed that secretion of organic acids is one of the main mechanisms which enable bacteria to mobilize the insoluble phosphate. Another mechanism by which the phosphorus solubilizing bacteria help plants to access the P is through excretion of protons or enzymatic production that solubilize insoluble forms of P or mineralize organic phosphorus and render it available to the plants for uptake [42] , [43] . Inoculation with endophytes increased phosphate solubilization and significantly improved plant growth [44] .…”
Section: Discussionmentioning
confidence: 99%